Working in partnership with people from under-represented groups to develop person-centred social and health care practices: methodological insights from the CICADA study - Rivas, Carol; Moore, Amanda P.; Anand, Kusha; Awan, Feryal; Begum, Samina; Heera, Neelam; Kumar, Sarabajaya; Shah, Sudhir; Shahid, Yesmin; Thomson, Alison (Frontiers in Health Services, 2025)
IntroductionThe COVID-19 pandemic both exposed and exacerbated the multiple pre-existing societal inequities for disabled people and those from minoritised ethnic groups in the UK, especially those who were on temporary visas, or were asylum seekers or undocumented migrants. Inequities in their health and social care were marked and poorly managed. Therefore, within the mixed-methods CICADA study, we explored their person-centred health and social care, with the primary aim of making recommendations for its improvement, focusing on the intersection of ethnicity, disability, and citizenship status. We used embodiment models of disability with an assets/strengths-based approach to develop useful person-centred solutions to issues. Person-centred care prioritises individuals’ diverse contexts and their inclusion in care decisions, thus its improvement is particularly suited to participatory research methods which formed a substantial component of the CICADA study; this alignment is the paper's focus as a methodological discussion.MethodsWithin the qualitative strand of the study, the topic of this paper, one aim was to explore the effectiveness of different types of collaborative approaches in successfully including recent migrants. Co-researchers from minoritised communities worked autonomously alongside the central team to conduct semi-structured interviews across England. Two community groups, working independently in parallel, interviewed further participants, produced autonomous reports, and helped practically. The study's public advisory group (PAG) joined the co-researcher team to facilitate knowledge exchange workshops (to develop mutual understanding) and mixed patient-professional co-design sessions (for patient-centred outputs and interventions).ResultsThe mix of different participatory methods proved an effective research approach and enabled the involvement of undocumented migrants and those of precarious migration status who would be excluded by other approaches. We were able to show, for example, how recent and undocumented migrants navigated UK healthcare systems with difficulty, meeting systemic cultural, bureaucratic and socioeconomic barriers that led to patient-provider misalignment rather than person-centred care. Co-design workshops produced collaboratively designed solutions, including improved communication strategies.DiscussionThe CICADA study underscored the importance of participatory methods in developing more person-centred care, by addressing structural inequities in research involvement that mirror those within health and social care services. It also showed the significance of choosing different participatory approaches depending on the specific needs, and some issues with their use in practice. Institutional constraints, such as funding and bureaucratic barriers, and time limitations, posed challenges to fully realising equitable participation. The study contributes to debates on the rigor and scalability of participatory methods and the impact on more inclusive, culturally attuned and person-centred care systems as well as on individual patient-practitioner interactions.ConclusionBy integrating participatory methods with an intersectional asset-based approach, the CICADA study advances person-centred care research, and advocates for systemic changes to enhance both research and care for minoritised groups.